Perceived suicide stigma, secrecy about suicide loss and mental health outcomes. Issue 4 (2nd April 2020) - Oexle, Nathalie; Feigelman, William; Sheehan, Lindsay
Abstract: Perceived suicide stigma and consequent secrecy about suicide loss could contribute to impaired mental health among suicide loss survivors. Using online survey data from 195 suicide loss survivors, higher perceived suicide stigma was associated with more grief difficulties, higher suicidality, and less personal growth. Secrecy partly mediated the association between perceived suicide stigma and grief difficulties as well as suicidality and completely mediated the association between perceived suicide stigma and personal growth. Our findings suggest that supporting suicide loss survivors in coping with perceived suicide stigma could reduce secrecy about suicide loss and by this improve their mental health outcomes.